ANALISIS WACANA KRITIS TEUN VAN DIJK DALAM CERITA RAKYAT TELUK PAKEDAI ASAL-MUASAL KEROAK BANGKAI - Rafi'i, Muhammad; Patriantoro; Gunawan (Universitas Hamzanwadi, 2025)
This research aims to analyse the discourse structure in the folklore of Asal-Muasal Keroak Bangkai by using Teun A. van Dijk's Critical Discourse Analysis (CDA) theory, which includes three main dimensions: text structure, social cognition, and social context. The method used in this research is descriptive qualitative with data analysis techniques developed by Miles and Huberman which consists of three research stages, namely data reduction, data presentation, and conclusion. Teun A. van Dijk's CDA approach was used to analyse the macro structure, superstructure, and micro structure of the folktales. The results showed that at the macro level, the story raised the theme of prudence and the consequences of human negligence in facing spiritual warnings. At the superstructure level, the story has a complete and structured narrative flow from introduction to conflict resolution. The microstructure shows the use of archaic diction, metaphorical language style, and stylistic elements typical of traditional oral literature. In terms of social cognition, the author conveys the moral message of the importance of preparedness and belief in the signs of the supernatural. The social context of the story reflects the belief system and cultural values of the local people who value traditions, myths, and the educational function of folklore. The overall analysis shows that folklore is not only a form of entertainment, but also a means of learning and in society.